Rural-Urban versus Urban-Rural - Xu Yixing; Xue Shanshan (Materia Arquitectura)
Chinese cities are semi-cities with two faces, a rural and an urban one. A place in the center of the city. At the same time, there is an urban quality within a totally green landscape. All cities are in fact in a situation of in-between. This creates a necessary vitality, and also an opportunity: a new type of reciprocal relationship between the urban and the rural face. This research describes ten Chinese cities with a dual nature experience of rural-urban. Although the cities have different histories, geographies, cultures, scales, and are in different stages of development, by locating their rural and urban faces, we can find clues to improve them.